Interleukin-6 and Interleukin-17 gene polymorphisms and celiac disease susceptibility - Ecevit, Çiğdem Ömür (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Ecevit ÇÖ. Interleukin-6 and Interleukin-17 gene polymorphisms and celiac disease susceptibility. Turk J Gastroenterol 2017; 28: 432-3.